A hybrid procedure of living donor liver transplantation for a pediatric patient with citrin deficiency. (7th February 2023) - Kosaka, Taiichiro; Soyama, Akihiko; Fujita, Takuro; Hara, Takanobu; Matsushima, Hajime; Imamura, Hajime; Adachi, Tomohiko; Hidaka, Masaaki; Eguchi, Susumu
Abstract: Background: The application of laparoscopic procedures in the liver surgery has been growing. We herein present the first case of a pediatric patient who underwent living donor liver transplantation (LDLT) using a hybrid procedure with hand‐assisted laparoscopic mobilization of the liver, subsequent explantation of the diseased liver, and implantation of the graft under direct vision. Methods: A 12‐year‐old girl with citrin deficiency was scheduled for LDLT with a left lobe graft. After making an 8‐cm upper midline incision, a 5‐mm trocar was placed at the umbilicus and the right upper abdomen. Mobilization of the right liver lobe was performed using a hand‐assisted laparoscopic surgery (HALS) procedure. After the extension of the midline incision, short hepatic vein dissection, encircling the right hepatic vein and hepatic hilum dissection was performed. Explantation of the liver and subsequent implantation of the liver graft were conducted under direct vision. Results: Since the operation, her normal activities of daily life have been maintained with a normal liver function. Subsequently, her secondary sexual characteristics have recovered without any wound‐related complications. Conclusions: A hybrid LDLT procedure was feasible for a pediatric patient. This procedure's benefits are considered meaningful for pediatric patients as it does not disrupt the rectus muscles or nerves and achieves cosmesis.